Choledochoduodenal fistula due to peptic duodenal ulcer diagnosed by X-barium meal study: interest of medical treatment - Mohamed Ali Chaouch; Karim Nacef; Mossab Ghannouchi; Mohamed Ben Khalifa; Asma Chaouch; Molk Abdelkafi; Saida Jerbi; Moez Boudokhane (The Pan African Medical Journal, 2018)

(untitled)
Peptic ulcer complication has decreased over le last years. Spontaneous bilio-digestive fistulas, in the absence of primary biliary disease, remain a very unusual complication of the upper digestive tract. The choledochoduodenal fistula is an extremely rare entity which can be caused by a duodenal peptic ulcer. It appears with the symptoms of peptic ulcer disease. They are diagnosed incidentally on radiological exams. It was suspected after finding pneumobilia on abdominal ultrasound and confirmed by X-barium meals study. The purpose of this observation is to report the case of a patient presenting a choledochoduodenal fistula diagnosed by X-barium meal to underline the importance of this radiological exam to diagnose this disease and to insist on the conservative treatment for choledochoduodenal fistula caused by a duodenal peptic ulcer. The prognosis of patients treated medically is good, although the fistula can remain asymptomatic. Angiocholitis and biliary sequelae remain rare and do not warrant prophylactic surgical treatment.